VARIATION OF ZOOPLANKTON IN THE HALBORI SPRINGS (TUNCELI, TURKEY) - Bulut, H.; Ozcan, E., I; Kilmac, C. (Aloki Applied Ecological Research and Forensic Inst Ltd, 2024)
This study examined certain water quality parameters and zooplankton fauna at two stations in Halbori Springs (Tunceli, Turkey), over a 12-month period from June 2022 to May 2023. The highest water temperature of 15.4 degrees C was recorded at Station 2 in August, while the lowest water temperature of 5.0 degrees C was recorded at Station 2 in January. The pH value of Halbori Springs ranged from 6.4 to 8.5. Dissolved oxygen varied between 8.1 and 11.9 mg/L during the study period. A total of 26 zooplankton species were identified in Halbori Springs. Nineteen of these species belong to Rotifera, five Cladocera and two Copepoda. According to the index analysis results of Station 1, the month with the highest species richness index, as measured by the Shannon Wiener H ' index, was October with a value of 1.97, while the lowest value was 0.45 in January. The highest value for the Margalef species diversity D index was 0.78 in October, and the lowest was 0.12 in January. According to the index analysis results of the station 2, the month with the highest species richness index, Shannon Wiener H', was September with a value of 1.68, while the lowest value was observed in January with 0.67. As for the Margalef species diversity index D, the highest value was recorded in September with 0.64, and the lowest value was observed in January with 0.12. In Halbori Springs, 1 species of Brachionus and 2 species of Trichocerca were found. The QB/T ratio was calculated to be 0.5, suggesting that the study area has oligotrophic characteristics.
Keywords: Rotifera; Cladocera; Copepoda; Halbori Springs; Tunceli; Turkey